Male age affects female mating preference but not fitness in the monandrous moth Dendrolimus punctatus Walker (Lepidoptera: Lasiocampidae). (5th November 2019) - Lai, Meng; Zhang, Shi‐Yu; Zhang, Yan‐Fang; Liu, Xing‐Ping
Abstract: It is widely accepted that male age can influence female mating preference and subsequent fitness consequences in many polyandrous species, yet this is seldom investigated in monandrous species. In the present study, we use the monandrous pine moth Dendrolimus punctatus to examine the effects of male age on female mating preference and future reproductive potential. In multiple male trials, when permitted free mating from an aggregation consisting of virgin males aged 0 (young), 2 (middle‐aged) and 4 (old) days, virgin females preferentially mate with young and middle‐aged males, although mating latency and mating duration are independent of male age. In single male trials, when virgin females are randomly assigned single virgin males of known age, a negative correlation is found between mating success and male age in this species. However, we find that male age also has no effect on mating latency and mating duration. Further fitness analysis reveals that females do not receive benefits in terms of oviposition period, total egg production, average daily egg production, percentage of egg hatching, longevity, expected reproduction and relative expected reproduction from mating with young and middle‐aged males compared with mating with old males. The results of the present study are the first demonstrate that females mated preferentially with younger males but gain no apparent fitness benefits in a monandrous moth species. Abstract : The present study is the first to report an age‐related female mating preference and fitness consequences in a monandrous moth species. Male age is a crucial factor affecting Dendrolimus punctatus female mating preference, showing that females significantly prefer young and middle‐aged males to old males for copulation. Male age does not affect the fitness of D. punctatus female in terms of mating latency, mating duration, oviposition period and other reproductive parameters.